Discontinuation of tumour necrosis factor inhibitors in patients with rheumatoid arthritis in low-disease activity: persistent benefits. Data from the Corrona registry. Issue 6 (3rd December 2014) - Kavanaugh, Arthur; Lee, Susan J; Curtis, Jeffrey R; Greenberg, Jeffrey D; Kremer, Joel M; Soto, Lilian; Etzel, Carol J; Cox, Vanessa; Yoshida, Kazuki; Reed, George W; Solomon, Daniel H
Abstract : Background: There is increasing interest in discontinuing biological therapies for patients with rheumatoid arthritis (RA) achieving good clinical responses, provided patients maintain clinical benefit. Methods: We assessed patients with RA from the Corrona registry who discontinued treatment with their first tumour necrosis factor inhibitor (TNFi) while in low-disease activity (LDA) or lower levels of disease activity. Patients were followed until they lost clinical benefit, defined as increased disease activity or change in RA medications. Duration of maintenance of clinical benefit was estimated using the Kaplan–Meier method. Cox proportional hazard models were assessed to identify factors related to maintenance of benefit. Results: We identified 717 eligible patients with RA from 35 656 in the Corrona registry. At discontinuation, patients had a median RA duration of 8 years, mean clinical disease activity score of 4.3±0.11; 41.8% were using TNFi as monotherapy. 73.4% of patients maintained benefit for >12 months after discontinuing therapy and 42.2% did so through 24 months. Factors predictive of maintaining clinical benefit in multivariate analysis included lower disease activity, less pain and better functional status at the time of TNFi discontinuation. Among 301 patients initiating their first TNFi within the registry, faster responders (ie, those who achieved LDA in 4 months or less) did better than slower responders (HR 1.54 (95% CI 1.17 to 2.04)). RA disease duration did not affect maintenance of clinical benefit. Conclusions: Discontinuation of a first course of TNFi may be associated with persistent clinical benefit. Half of patients maintained response through 20 months. Several patient characteristics may help predict persistent benefit.